Using Whatsapp in Learning During Covid-19: Voices of Kindergarten Students’ Parents in Indonesia - Puji Siswanto; Nugroho, Arief Styo; Jambari, Obay; Usmaedi, Usmaedi; Cahyono, Habib (Universitas Majalengka, 2024)
The advancement of information and communication technology (ICT) has big effects on human life in many facets, one of them is in education. However, the use of this technology left some problems faced by its users. Therefore, this study aims to explore in-depth the kindergarten student parents’ perception of the use of WhatsApp in the teaching and learning process during the COVID-19 pandemic in Indonesia. The study employed the exploratory study which engaged twenty-nine students’ parents in Lebak - Indonesia where online learning using WhatsApp was implemented. Then, six participants were voluntarily involved in the interview. The questionnaire and semi-structured interview were administered in collecting the data. The data from the questionnaire were analyzed in percentage while the content analysis technique was used in analyzing the data from the semi-structured interview. From the data analysis, this study reveals two major research findings. Firstly, the use of WhatsApp helped students in learning during the COVID-19 pandemic and physical distancing, establishes student and teacher communication, Secondly, technical problems were found such as unstable internet connection, student-teacher communication and interaction are not maximized, and lastly, after a long period, the students got bored. In brief, the use of WhatsApp can be used as an alternative teaching platform in the COVID-19 age on the one hand, on the other hand, its’ usage faced barriers such as unstable internet connection.